PENGELOLAAN SISTEM KEARSIPAN ELEKTRONIK "SIMANSU" DI BADAN PENANGGULANGAN BENCANA DAERAH PROVINSI JAWA TIMUR - Nurrachmaningrum, Aulia Putri; Lestari, Yuni (Jurnal Inovasi Administrasi Negara Terapan (Inovant), 2023)
The electronic archive system is a form of advancement in information technology as evidence and a form of accountability. The purpose of this study was to describe the management of the electronic archive system "SIMANSU" at the Regional Disaster Management Agency of East Java Province. The type of research used is a descriptive approach with a qualitative approach. The focus of this research uses Read & Giin's theory (in Winata, 2016) there are 4 phases of the electronic archive journey including: Creation and Storage, Distribution and Use, Maintenance, Disposition The results of this study indicate that the management of the SIMANSU electronic archive system includes: (1) Creation and Storage through the SIMANSU system is quite good, however, it is constrained in the process of storing incoming letters with numbers that are too long so that when saving through the SIMANSU system will be cut off by the system, the process of creating task orders (SPT) in the SIMANSU system does not have a special signature template for the head of each field and the process of storing outgoing letters in the SIMANSU system is no longer used because the storage is input according to the system order or randomly. 2) Distribution and use can be seen that the distribution carried out by the Regional Disaster Management Agency of East Java Province is carried out directly and by courier delivery, but in using the SIMANSU system there are obstacles, namely processing the use of incoming letters which cannot enter letter numbers that are too long so that the use process in storing letters will be cut off by the system and the unavailability of signature templates according to the leaders of each field. (3) Maintenance, maintenance of the SIMANSU system has been carried out regularly, however, it is constrained by the absence of a budget. (4) Disposition, disposition through the SIMANSU system has been in accordance with the instructions of the Chief Executive but is constrained by the use and storage process in the SIMANSU system so that the delivery of the disposition results by including a letter number that is too long cannot be detected by the system. Keywords: Archives, Electronic Filing System, SIMANSU